AKIBAT PENDAFTARAN JAMINAN FIDUSIA DAN KEKUATAN HUKUM SERTIFIKAT JAMINAN FIDUSIA YANG DITERBITKAN OLEH KANTOR PENDAFTARAN FIDUSIA - Cintya Virgyanti, Ni Putu; Adi Yaryani, Ni Nengah (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Transfer of ownership over property which is considered as object of fiduciary shall not be juridically proven by parties’ act, but by registration of object of fiduciary warrant in Fiduciary Registration Office by the applicant. As prove of registration, the applicant shall receive Fiduciary Warrant Certificate. Certificate shall act as means of execution by those who vest the rights directly towards the warranted object in the circumstances of breach of contract. By applying normative legal research, this paper shall illustrate the legal consequences of fiduciary warrant registration which later be legally approved by the certificate issued by the Fiduciary Registration Office. Registration shall ensure the legal certainty for creditors and protecting the applicant from the third party. Besides, the issuance of certificate shall also serve as continuation of process which entails executorial power which is equally binding compared to that of judgments of court.
Keywords: Certificate, Fiduciary Warrant, Legal Validity, Registration